Монголын Нууц Товчоо ба метафор - Ж.Лувсандорж (Acta Mongolica, 2008)
The Secret History of the Mongols has been translated into many so-called world languages (for some of them 2-4 times). The meanings of old expressions and metaphors incorporating the patterns of the ancient language and thoughts of nomads have been forgotten or misunderstood quite frequently in the modern language. Since this process of misuse started even in the 13th century, mistakes were reflected already in the first Chinese translation. In other words, the first Chinese word-to-word translation has a number doubtful, sometimes clearly mistaken, expressions Moreover some 40 words were left without a corresponding literal translation and it is not a secret that the translators of the SHM into the foreign languages restricted themselves forcedly with the Chinese meaningful translation. It is clear what happens if metaphors are translated literally, i.e word-by-word. In Kozin's Russian translation the poctic passages were translated freely keeping the poctical sense, but providing with the underlined word-by-word translation in brackets. This type of translation is claimed by the author as the most relevant, even though the Kozin's literal translation is not free of inappropriate moments